Pengaruh Model Cooperative Script Terhadap Kemampuan Menyimak Teks Berita Siswa : Cooperative Script, Menyimak, Berita - Noibe Halawa (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
The purpose of this study was to find out whether there was an effect of the cooperativescript model on the ability to listen to news texts for Grade VIII students of Hoya Sejahtera Private Middle School. The type of data used in this study is quantitative data in the form of primary data, namely data collected by researchers in the form of student learning outcomes tests which are carried out before carrying out learning activities called the initial test (pretest) and the final test (post test) which is carried out after the learning process is carried out. Based on the results obtained and the analysis of the research data and the hypothesis testing, conclusions can be drawn. First, the average learning achievement of Indonesian using the cooperative script learning model for class VIII students of Hoya Sejahtera Private Middle School in the 2019/2020 academic year is 87.6, including at a good level of ability. Second, the average student learning outcomes in the Indonesian language subject using conventional learning at Hoya Sejahtera Private Middle School is 67.31, which is included at the moderate level of ability. And third, the results of the hypothesis test turned out to be tcount > ttable or 7.682> 2.660, so it can be concluded that there is a significant effect on the cooperative script learning model on the ability to listen to news texts for class VIII students of Hoya Sejahtera Private Middle School.